2021
DOI: 10.53935/2641-533x.v4i2.158
|View full text |Cite
|
Sign up to set email alerts
|

Self-Concept, Self-Efficacy and Self Esteem as Predictors of Academic Performance in Mathematics among Junior Secondary School Students in Edo State

Abstract: This study examined Self-Concept, Self-Efficacy, and Self-Esteem as Predictors of Academic Performance in Mathematics among Junior Secondary School Students in Edo State. The main purpose of the study is to determine the relationship between self-concept and academic performance in mathematics of Junior Secondary School students in Edo state. The study adopted the correlation research design. A sample of 3,639 was drawn from a population of 36,615 junior students in Edo state. The data generated for the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…More simply, self-efficacy is the belief that one can use one's talents to attain a goal in a given situation. It has been proposed that self-efficacy is task-specific self-esteem (Asika, 2021). Self-efficacy theory is based on the idea that people are more likely to participate in activities for which they have a high level of self-efficacy and less likely to participate in activities they do not (Yang et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…More simply, self-efficacy is the belief that one can use one's talents to attain a goal in a given situation. It has been proposed that self-efficacy is task-specific self-esteem (Asika, 2021). Self-efficacy theory is based on the idea that people are more likely to participate in activities for which they have a high level of self-efficacy and less likely to participate in activities they do not (Yang et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies on the determinants of academic performance among high school students have underscored the importance of multiple factors. Asika (2021) research underlined the importance of self-efficacy and academic self-concept in predicting intellectual achievement among high school students. The results of this study indicated that the convictions held by students regarding their aptitude and assessments of their academic competencies are pivotal factors in determining their academic achievement.…”
Section: Chatgpt As An Academic Support Toolmentioning
confidence: 99%